EDP managing a new electricity era: the birth of ocean winds - managing the regulatory and technological risks of offshore wind development - Vieira, Susana Mafalda Dias Albuquerque Guedes (2022)
With EDP’s entrance into the renewable energy market solar and wind energy became pillars of the renewable energy strategy. Jumping directly from onshore to floating offshore, EDP displayed a strategic core of innovation and geographical expansion. This case details their start on floating offshore from Wind Float Atlantic, their first main partnership in the sector to their eventual joint venture with Engie on Ocean Winds with a focus on offshore wind. This thesis details the path EDP has taken while analyzing their actions, meanwhile the report portion analyzes risks and opportunities on the offshore market overall and for joint ventures.